2014
DOI: 10.4236/msa.2014.510074
|View full text |Cite
|
Sign up to set email alerts
|

Macrosegregation Quality Criteria and Mechanical Soft Reduction for Central Quality Problems in Continuous Casting of Steel

Abstract: In order to study the central quality of continuously cast tool steel slabs, the simple model has been developed to simulate the macrosegregation quality criteria. The model calculates different quality criteria such as average macro-segregation level criterion "ASL", its fluctuation level "FSL" and its segregation quality number "SQN". These criteria are calculated based on the previous measurements of carbon and sulfur concentrations distributions in final region of spray zones and centerline area of lower a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Moreover, Figure 4 gives the local topography of shrinkage cavity shown in Figure 1 using SEM analyses. It is seen that there are many columnar crystals present inside of the cavity, which means that the current parameters of soft reduction listed in Table 3 cannot sufficiently compensate the volume contraction at the final solidification stage [18,19]. Based on the discussions above, it can be concluded that the technique parameters of F-EMS and soft reduction have not met the critical conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, Figure 4 gives the local topography of shrinkage cavity shown in Figure 1 using SEM analyses. It is seen that there are many columnar crystals present inside of the cavity, which means that the current parameters of soft reduction listed in Table 3 cannot sufficiently compensate the volume contraction at the final solidification stage [18,19]. Based on the discussions above, it can be concluded that the technique parameters of F-EMS and soft reduction have not met the critical conditions.…”
Section: Introductionmentioning
confidence: 97%
“…The internal quality of the bearing steel bloom has great influence on its reliability and service life due to the inheritance of the defects from the bloom, such as shrinkage porosity, center segregation, and V-shaped segregation to the subsequent rolling product. Generally, homogenization of the chemical composition by means of electromagnetic stirring (EMS), pulsed magneto-oscillation (PMO), low superheat casting, low secondary cooling intensity, etc., is the most well-known approach to minimize the center segregation [1][2][3][4][5][6]. This approach aims to produce large ratio of equiaxed grains during solidification and normally is an effective way to reduce center segregation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to respond instantaneously because most process parameters are difficult to control during operation. Mold taper, 11,12 spray cooling, 13,14 and soft reduction systems 15,16 are often set before starting casting and focus on steady-state solidification. Corrective action, such as responding to alarms from online breakout detection systems, for example, typically involve suddenly slowing the casting speed, which can lead to quality problems due to the transient conditions.…”
Section: Introductionmentioning
confidence: 99%